2002
DOI: 10.1177/088626002237399
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Expectancies Among Sexually Coercive College Men

Abstract: This study investigated the relationship between college men's self-reported histories of coercive sexual behavior, alcohol consumption, and alcohol expectancies regarding sexual behaviors. Hypotheses were (a) history of sexually coercive behavior would be associated with more alcohol consumption, (b) sexually coercive men would hold greater alcohol expectancies for sexual behaviors, and (c) alcohol expectancies would moderate the relationship between alcohol consumption and sexual coercion. In addition, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…The alcohol dosing procedure used in the current investigation allows general inferences about the influence of alcohol on sexual perception but does not allow us to determine the extent to which these effects are due to alcohol pharmacology or expectancies (Brown, Goldman, Inn, & Anderson, 1980). Sexual decision making is clearly one arena in which expectancies about the influence of alcohol play an important role (Wilson, Calhoun, & McNair, 2002). An important future investigation will parse the relative contribution of expectancy versus pharmacological effects of alcohol on men's perception of women.…”
Section: Discussionmentioning
confidence: 99%
“…The alcohol dosing procedure used in the current investigation allows general inferences about the influence of alcohol on sexual perception but does not allow us to determine the extent to which these effects are due to alcohol pharmacology or expectancies (Brown, Goldman, Inn, & Anderson, 1980). Sexual decision making is clearly one arena in which expectancies about the influence of alcohol play an important role (Wilson, Calhoun, & McNair, 2002). An important future investigation will parse the relative contribution of expectancy versus pharmacological effects of alcohol on men's perception of women.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, compared with nonsexually aggressive men, sexually aggressive men expect that alcohol use will have a stronger global positive effect (Aromaki & Lindman, 2001; Menard, Hall, Phung, Ghebrial, & Martin, 2003). Sexually aggressive men are also more likely than nonsexually aggressive men to report that alcohol use will enhance their sexuality (McMurran & Bellfield, 2003; Palmer, McMahon, Rounsaville & Ball, 2010; Wilson, Calhoun, & McNair, 2002). Furthermore, research conducted within the laboratory suggests that compared with men who do not expect to consume alcohol, men who expect to consume alcohol report more interest in sexual violence (George & Marlatt, 1986), indicate more sexual arousal in response to violent media (Briddell et al, 1978), and display longer delays in recognizing that the perpetrator of a hypothetical date rape should refrain from further advances (Marx, Gross, & Juergens, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Bernat et al (1998) found that sexually aggressive men, while listening to aural narratives depicting date rape, were more permissive of sexually aggressive behaviour if the couple had consumed alcohol prior to the incident. Wilson, Calhoun, and McNair (2002) looked at alcohol consumption, alcohol expectancies on sexual behaviour, and sexual aggression in a college sample and found that men who had engaged in sexual aggression reported consuming more alcohol than men who had not engaged in sexual aggression. Sexually aggressive men also expected that alcohol would have a greater effect on sexual behaviour.…”
Section: Alcoholmentioning
confidence: 99%